A Product Production and Transfer Application with Blockchain - Hazim IŞCAN; Ömer ÇAKICI (International Journal of Applied Methods in Electronics and Computers, 2022)
In traditional software systems, user information is kept in databases of the system. Much of this information is critical. Theft of data and getting into the hands of malicious people can cause big problems. The most efficient way to get rid of this is to keep the information encrypted, to decrypt the encrypted information with private keys that are not registered in the system, to never access the encrypted information without the private key, and to use it in platform-independent systems. Blockchain technology offers us this system. Blockchain technology, which can be applied very easily in economic fields or systems with transparent data policy of priority, is also the basic structure of cryptocurrencies. Its importance is increasing day by day in the world and it is increasing its weight in banking-finance, voting, asset management and company-specific software systems. In this study, encryption methods of Blockchain technology, data verification approaches, wallet creation, the roles of public and private keys in wallets in the system, their authorization, the formation of transfers within a certain rule and their verification by a third party after the transfer are discussed theoretically and practically. An application was developed on peer-to-peer transfers of white goods production and products, which were fictionalized as a scenario, and Blockchain technology was applied.